Anatomia de uma epidemia: migração, descaso público e a reemergência do Sarampo no Amazonas (2017 a 2019) - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Measles is a serious acute infectious disease, transmissible and highly contagious, caused by a virus in the family Paramixoviridae, genus Morbillivirus, which used to be very common in childhood in the pre-vaccination era. It has no specific treatment. Medications are used to reduce the discomfort caused by the symptoms of the disease. The only way to break the chain of transmission is through vaccine immunization. As a cosmopolitan infection, the Measles Eradication Plan was adopted in all regions of the Americas, advocating common research actions for all countries. However, measles remains a public health problem in developing countries. The most important strategy for its control is vaccination in general, recommended by the World Health Organization (WHO). But even with the effective availability of the vaccine, some developing countries find it difficult to interrupt the circulation of the virus through adequate vaccination coverage. In Brazil, the measles vaccine was introduced in 1967 and 1968, and was used in a non-systematic way until 1973, when the National Immunization Program (PNI) was created. There is evidence of interruption of autochthonous measles virus transmission in the country since 2000, however, the Ministry of Health confirmed several imported cases between 2001 and 2014 and a new outbreak in 2018, which coincides with the increase in immigration from from a country where there were already outbreaks of the disease in previous years. The objective of this study was to relate the re-emergence of measles to vaccination coverage in the state of Amazonas, in the years 2017 to 2019. As a methodology to achieve the objective proposed in that study, a bibliographic survey of literature dealing with the theme of measles was carried out. , and newsletters in public institutions to identify the incidence and prevalence rates of measles in Brazil and Amazonas. It began with a brief description of the concept and formation of the nation-state, territory and border, in order to provide a better understanding of the Immigration process, which figured as an important topic in the study; reflected on the consolidation of the Modern State based on the Westphalia Accords, treaties that were considered a milestone for the recognition of the sovereignty of States, in order to lead to a better understanding of the formation of the border; analyzed the formation of the Brazilian territory from the occupation of land, to confirm Ratzel's thought on this category, which is one of the basic concepts of geography, when he states that the soil and society are linked and the union of both forms the territory. Surveys of the laws governing epidemics in Brazil were also carried out with the Ministry of Health, especially measles, in order to identify the public policies applied in Brazil and in the State of Amazonas. The results show that the vaccine coverage rate was in a precipitous drop and that a percentage considered low had complete immunization against measles. Based on the results achieved, it is proposed to reflect on the structuring of the health sector and its importance in combating epidemics and to promote reflection on Public Neglect in epidemiological control at the borders of Brazil in order to prevent and prevent new outbreaks.
Keywords: Política pública - Manaus (AM); Sarampo - Vacina; Vacinação - Amazonas; CIENCIAS HUMANAS: GEOGRAFIA: GEOGRAFIA HUMANA; Geografia; Migração; Saúde; Sarampo; Políticas públicas